Learn Raspberry Pi Programming with Python : Learn to Program on the World's Most Popular Tiny Computer - Donat, Wolfram (Technology in action series., 2018)
"Learn how to program your nifty new $35 computer to make a web spider, a weather station, a media server, and more. This book explores how to make a variety of fun and even useful projects, from a web bot to search and download files to a toy to drive your pets insane. Even if you're completely new to programming in general, you'll see how easy it is to create a home security system, an underwater photography system, an RC plane with a camera, and even a near-space weather balloon with a camera. You'll learn how to use Pi with Arduino as well as Pi with Gertboard, an expansion board with an onboard ATmega microcontroller. Learn Raspberry Pi Programming with Python has been fully updated in this new edition to cover the features of the new boards. You'll learn how to program in Python on your Raspberry Pi with hands-on examples and fun projects. What You'll LearnSet up your new Raspberry PiBuild unique projects across a range of interestsProgram basic functions and processes using PythonWho This Book Is ForReaders who want to learn Python on a fun platform like the Pi and pick up some electronics skills along the way. No programming or Linux skill required, but a little experience with Linux will be helpful. Readers familiar with the 1st edition will enjoy the updated information in this new edition."- Resumé vydavatel